1989
DOI: 10.3928/1081-597x-19891101-06
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Descriptors of Corneal Shape Derived from Computer-assisted Analysis of Photokeratographs

Abstract: The goal of this retrospective study was to derive clinically useful quantitative measures of corneal shape from computer-assisted analyses of photokeratoscope photographs. Algorithms were developed to determine a new index of corneal symmetry, the Surface Asymmetry Index (SAI). The SAI correlated well with best spectacle-corrected visual acuity and may be useful clinically for predicting the level of spectacle-corrected visual acuity that could be expected based on the corneal surface topography in the otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(32 citation statements)
references
References 7 publications
0
27
0
5
Order By: Relevance
“…Several indices, algorithms, and even neural network approaches that take the geometry and optical properties of the anterior corneal surface into account have been developed for keratoconus diagnosis and detection. 4,[6][7][8][35][36][37][38][39][40][41][42][43] In addition, new mathematic methods to reconstruct anterior corneal geometry have been developed. 44 However, it has been shown that the underlying alterations in corneal biomechanics in eyes with keratoconus induce changes in the geometry and optical properties of the anterior corneal surface 22,45 but also have an impact on the posterior corneal surface, 4,[9][10][11][12]14,15 corneal volume, 16,17 and pachymetry.…”
Section: Discussionmentioning
confidence: 99%
“…Several indices, algorithms, and even neural network approaches that take the geometry and optical properties of the anterior corneal surface into account have been developed for keratoconus diagnosis and detection. 4,[6][7][8][35][36][37][38][39][40][41][42][43] In addition, new mathematic methods to reconstruct anterior corneal geometry have been developed. 44 However, it has been shown that the underlying alterations in corneal biomechanics in eyes with keratoconus induce changes in the geometry and optical properties of the anterior corneal surface 22,45 but also have an impact on the posterior corneal surface, 4,[9][10][11][12]14,15 corneal volume, 16,17 and pachymetry.…”
Section: Discussionmentioning
confidence: 99%
“…The following corneal topographic parameters and keratoconus indices were obtained from Medmont-E300 (Medmont, Camberwell, Australia, Medmont studio V.6.1.1.4—all captured exams were analysed with this version), Placido ring-based axial power maps, for the first (baseline) and most recent (final) reviews for all eyes that met the inclusion/exclusion criteria; apical keratometry (Kmax), steep simulated keratometry (Ksteep), flat simulated keratometry (Kflat), inferior-superior dioptric asymmetry (I-S),8 surface asymmetry index (SAI)9 and surface regularity index (SRI) 10…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the surface asymmetry index (SAI) is the difference in corneal powers between points on the same ring 180 degrees apart. The power distribution across a normal corneal surface is fairly symmetric, and has been reported to increase in corneal disorders, thus indicating the progression of disease state in conditions such as keratoconus and pellucid marginal degeneration [17]. The calculation equations for the two indices are shown in Fig.…”
Section: Corneal Topography Analysismentioning
confidence: 99%